Double heterozygosity of novel variants found in patients with severe clinical phenotype of cardiovascular disorders - Slavica Josifovska; Radoslava Vazharova; Lubomir Balabanski; Maxim Malinov; Anna Kaneva; Sasho Panov; Savina Hadjidekova; Draga Toncheva (Biotechnology & Biotechnological Equipment, 2018)
Cardiovascular diseases (CVD) comprise a broad range of disorders of the heart and blood vessels. In this study, we used next-generation sequencing with a panel that includes 174 genes connected to CVD in order to investigate the possible genetic causes that underline some clinical phenotypes and their severity. Two patients were found with double heterozygosity, each carrying one new variant. One patient with supravalvular aortic stenosis has novel ELN: c.890-1G>A and a known variant SCN5A: p.Gly9Val in a heterozygous state, whereas another patient with hypertrophic cardiomyopathy has a heterozygous novel CACNA1C: p.Arg514Gly and a known SCN5A: p.Arg800His variant. This method proved to be useful in determining the mutation status in correlation with the severity of the clinical phenotype and can further clarify cases where the clinical status could not be explained only by single gene mutation detected by standard methods.